Tourism Geography of Landlocked Himalayan Countries: A Case Study of Nepal and Bhutan - Dr.Ali Shafeeq Hameed Taha (Journal of College of Education, 2026)
Nepal and Bhutan lie at the heart of the Himalayas and are mountainous landlocked countries with no access to the sea, bordered only by China and India. Despite their geographic isolation and rugged terrain, both nations have succeeded in building a distinctive tourism identity, centered around mountain, spiritual, and eco-tourism. This research aims to study the tourism geography of Nepal and Bhutan and analyze the impact of their mountainous, landlocked location on shaping tourism patterns. It also offers a comprehensive comparison of the natural and human tourism assets of both countries and the policies adopted to manage tourism. Tourism geography is an important branch of economic geography, as it highlights the natural and human factors that form the core of tourism attraction. This study considers Nepal and Bhutan as unique case studies in terms of location, terrain, and culture. Both are non-coastal countries in the heart of South Asia, surrounded by towering mountain ranges that pose a challenge to tourist access, yet give them a unique character as global tourist destinations. The research analyzes the geographical characteristics location, terrain, climateas well as the cultural and spiritual elements, and the diversity of tourism patterns such as eco-tourism, religious tourism, and adventure tourism. The study adopts a comparative analytical geographical methodology and utilizes international data and previous studies to provide a comprehensive perspective. The findings conclude that geography, rather than being a barrier, has become a main attraction in shaping the unique tourism experience in both countries, despite differences in political and.
Keywords: Nepal, Bhutan, Tourism Geography, Mountainous Countries